Metabolic reprogramming orchestrates an immunosuppressive microenvironment in anaplastic thyroid cancer: mechanisms and clinical perspectives - Xia, Jinkun; Zhai, Baowei (Frontiers in Immunology, 2026)
Anaplastic Thyroid Carcinoma (ATC) represents one of the most aggressive and lethal human malignancies, characterized by rapid progression, profound therapy resistance, and a dismal prognosis. Recent advances have underscored metabolic reprogramming as a cornerstone of ATC pathogenesis, enabling tumor cells to adapt to a hostile microenvironment, sustain proliferation, and evade immune destruction. This review systematically delineates how metabolic alterations in ATC—spanning enhanced glycolysis, deregulated lipid metabolism, and aberrant amino acid utilization—orchestrate a profoundly immunosuppressive tumor immune microenvironment (TIME). We explore the mechanistic links between tumor metabolism and immune dysfunction, including nutrient competition-induced energy deficits in effector immune cells, accumulation of immunosuppressive metabolites, and metabolic regulation of immune checkpoint expression. Furthermore, we discuss the impact of metabolic crosstalk on immune cell phenotypes, fostering the recruitment and polarization of pro-tumorigenic immune populations such as M2 macrophages, regulatory T cells, and myeloid-derived suppressor cells. Clinically, we highlight the therapeutic promise of targeting key metabolic nodes and review emerging combination strategies that integrate metabolic inhibitors with immune checkpoint blockade to overcome resistance and enhance antitumor immunity. By synthesizing foundational insights with cutting-edge preclinical and clinical evidence, this review aims to provide a cohesive mechanistic framework and identify novel, metabolism-based therapeutic vulnerabilities for precision immunotherapy in ATC.